Transcendental Justice Law: The Relation of Law and Justice - Syaifuddin Zuhdi (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2021)
The purpose of this article is to explain the relation between law and justice in order to realize a law that is transcendental justice. The method used is a normative method or literature study with a philosophical approach. The findings from this discussion are that justice is not only talking about benefits and harm such as the principles of justice according to Bentham and Rawls, a good law is a law that is able to represent the values of God’s justice, such as equality (egalitarianism), balance, harmonization, ta’awun (helping each other), recognizing and respecting each other’s rights and obligations, and so on, both in the text of the law, as well as in its application. On the other hand, bad law is a law that deviates(deviative) from the values of justice. This law is like a parasite that only causes damage to society. Justice and truth are not the main pattern, but power and worldly satisfaction are the pattern